2005
DOI: 10.1111/j.1469-8986.2005.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive difference in ERPs reflects independent processing of visual changes

Abstract: To elucidate the nature of the processing of visual stimulus changes, ERPs were recorded while 12 participants performed an S1-S2 matching task with multifeature stimuli. Each trial consisted of two sequentially presented stimuli (S1-S2), where S2 was either the same as S1, different from S1 only in color, different only in shape, or different in both color and shape. The four trial types were presented in random order with equal probability, and participants responded to one of these types in separate blocks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
48
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 55 publications
13
48
2
Order By: Relevance
“…The peak latency and scalp-distribution of the positivity are consistent with change-related positivity observed in previous studies (e.g., Fonteneau and Davidoff, 2007;Fu et al, 2003;Kimura et al, 2005aKimura et al, , 2005bKimura et al, , 2006aKimura et al, , 2006bKimura et al, , 2006cWang et al, 2003). The present finding that change-related positivity was elicited by size decrements suggests that such change-related positivity could be elicited when stimulus changes engage memory-comparison-based change detection but do not strongly engage refractoriness-based rareness detection.…”
Section: An Erp Correlate Of Memory-comparison-based Change Detectionsupporting
confidence: 77%
See 4 more Smart Citations
“…The peak latency and scalp-distribution of the positivity are consistent with change-related positivity observed in previous studies (e.g., Fonteneau and Davidoff, 2007;Fu et al, 2003;Kimura et al, 2005aKimura et al, , 2005bKimura et al, , 2006aKimura et al, , 2006bKimura et al, , 2006cWang et al, 2003). The present finding that change-related positivity was elicited by size decrements suggests that such change-related positivity could be elicited when stimulus changes engage memory-comparison-based change detection but do not strongly engage refractoriness-based rareness detection.…”
Section: An Erp Correlate Of Memory-comparison-based Change Detectionsupporting
confidence: 77%
“…Second, although the present results support the notion that change-related positivity reflects memory-comparison-based change detection (e.g., Fonteneau and Davidoff, 2007;Kimura et al, 2005aKimura et al, , 2005bKimura et al, , 2006aKimura et al, , 2006bKimura et al, , 2006c, except for S1-S2 matching studies (Fu et al, 2003;Kimura et al, 2005aKimura et al, , 2005bKimura et al, , 2006aKimura et al, , 2006bKimura et al, , 2006cWang et al, 2003) and some oddball studies (Fonteneau and Davidoff, 2007;Kimura et al, 2006c) Finally, the present study found three early change-related effects (change-related negativity, change-related positivity, and frontal positivity). At present, the precise relationship between attentional capture and these early change-related effects is still unclear.…”
Section: Future Researchcontrasting
confidence: 39%
See 3 more Smart Citations